Properties, theoretical study and crystal structure of 3‐benzothiazole‐9‐ethyl carbazole. (7th February 2016) - Gu, Yingchun; Lin, Dayong; Fei, Xuening; Wang, Cuihong; Li, Ling; Tang, Yalin; Zhou, Jianguo
Abstract: The title compound of 3‐benzothiazole‐9‐ethyl carbazole was synthesized by the reaction of 3‐aldehyde‐9‐ethyl carbazole and 2‐aminothiophenol. The compound was characterized by 1 H nuclear magnetic resonance (NMR) and mass spectrometry (MS). Its crystal structure was obtained and determined by single crystal X‐ray diffraction. The results showed that the crystal belongs to the orthorhombic crystal system and the cell parameters of space group P2(1)2(1)2(1) were a = 5.6626 (12) Å, b = 12.606 (3) Å, c = 22.639 (5) Å, α = 90°, β = 90°, γ = 90°, V = 1616.0 (6) Å 3, Z = 4, Dc = 1.350 mg/m 3 . The UV–vis and fluorescence spectra were also studied preliminarily. The fluorescence spectra of the title compound with bovine serum albumin (BSA) showed that BSA could be marked with the compound and the stability constant between them was 0.82 × 10 7 M −1 . Meanwhile, the crystal and molecule were theoretically surveyed by density functional tight‐binding (DFTB). The results showed that there was an orbital overlap for lowest unoccupied molecular orbital (LUMO) between the neighbouring molecules for the crystal, which is different from the molecule structure. It was also showed that the crystal structure is a non‐conductor. Copyright © 2016 John Wiley & Sons, Ltd.